Controlling Domain Wall Nucleation and Propagation with Temperature Gradients - Altbir-Drullinsky, D (American Institute of Physics, 2016)
Field driven nucleation and propagation of transverse domain walls (DWs) in Fe nanowires under thermal gradients were studied using Monte Carlo simulations. Simulations identified that thermal gradients contribute to stabilizing nucleation of multiple DWs. The results also showed that the correct combination of a magnetic field and temperature gradients applied along a wire can provide a high degree of control over the direction, velocity, and acceleration of DW propagation, which is of paramount importance for technological applications. © 2016 Author(s).